A winning BID? The effects of a BID-inspired property owner collaboration on neighbourhood crime rates in Malmö, Sweden - Kronkvist, Karl (Crime prevention and community safety, 2020)
The business improvement district (BID) model has spread rapidly worldwide and has recently caught the eye of Swedish politicians and practitioners as a feasible approach to reduce crime in urban neighbourhoods. Research on the crime-preventive effects of BIDs is, however, limited to a handful of US studies, and there is a lack of research from European contexts. The aim of the present study is to fill gaps in knowledge by examining the crime-preventive effects of a BID-inspired property owner collaboration (BID-Malmö) implemented in a residential neighbourhood in Malmö, Sweden. Based on the use of a difference-in-difference estimator and weighted displacement quotients, our results demonstrate a significant reduction in crimes reported to the police in the intervention neighbourhood relative to control areas, with signs of spatial diffusion of benefits rather than displacement of crime to adjacent areas. This result is, however, mainly driven by a decrease in reported incidents of vandalism, while no effect is observed in regard to violent crime in public places. Implications of the findings and further research are discussed.